Regionális fejlettségi különbségek összefüggése a kivándorlás lehetséges gazdasági hatásaival - Koudela, Pál (Közép-Európai Közlemények, 2015)
Emigration is usually much less important subject than immigration and its different economic-structural reasons and feedback to some regions is even more so. Some countries like Hungary even don't collect emigration data. Nevertheless, regional differences give chance, at least theoretically, through historical and inner migration analogues and by case studies, to analyze how emigration affect their future. Along with traditional regional economic development indicators I am considering the migration context of structural differences in this study. Higher education plays a key role in international migration. Counties in Hungary with big cities and institutions of higher education increase inner migration flows from underdeveloped counties. This increases their participation in international migration by the high international educational mobility in these institutions.